Optimizing solar energy for houses with slanting type roofs - Sabri Salim, Muhammed (International Journal of Engineering and Technology, 2018)
During the daily sun cycle, the falling rays are of varying intensity on the solar panel reducing the energy generated from it. This is evident in the energy production of solar panels that are installed on the slanted surfaces of homes scattered in the rain regions of the world. In this research, the reasons for the low efficiency of energy production of solar panels that are installed on the A-frame designs of homes were studied and solved. The design of an integrated tracking system is developed based on fuzzy logic control using an open source code that can be easily modified. The performance and characteristics of the solar tracking device are tested experimentally to test its suitability for use with slanted roofs homes. The integrated solar localization system offers economical and efficient solar monitoring, as well as open source programming, which allows for future improvements and changes. In addition, the single-axis fuzzy tracking system was good for moving both panels in less than five seconds towards the sun. The adoption of the proposed design provides an extremely accurate tracking system and therefore, maximizes the potential of power generated by the solar panel since it will meet the sun's rays from dawn to dusk. The economic effect of the proposed design is to approximately double the value of electrical power received compared to the fixed design.Â Â